PENETAPAN VARIABEL JARAK SEMPADAN PANTAI UNTUK ANALISIS MULTI KRITERIA SPASIAL DI KOTA SERANG - Adi, Luwi Wahyu (Universitas Negeri Padang, 2024)
Spatial multi-criteria analysis (SMCA) has been used by researchers to conduct research in geography. One of them is how to determine protected areas in an area, namely Serang City, Banten. This research aims to review what the determination of the coastal boundary distance variable looks like for the SMCA analysis process. The criteria were determined through a literature review, both in terms of applicable regulations and scientific articles. Based on the results of the review, it was concluded that the coastal boundary variable is measured from the shoreline towards the mainland by 100 - 300 meters. The minimum criterion value is 100 meters, while the criteria values of 200 meters and 300 meters can be adjusted according to the level of hazard risk. The area along the north coast of Serang City bordering the Java Sea is included in the protected area. The area must be preserved and development restricted.